Arterial oxygen saturation in healthy newborns delivered at term in Cerro de Pasco (4340 m) and Lima (150 m) - Gonzales Gustavo F; Salirrosas Amelia (BMC, 2005)
Abstract Background High altitude is associated with both low pulse oxygen saturation at birth and more pre-term deliveries. The present study was performed to determine pulse oxygen saturation in newborns at term in Cerro de Pasco (4340 m) and Lima (150 m) to test the hypothesis that low pulse oxygen saturation at birth at high altitudes was not observed at term deliveries. Methods The present study was designed to determine pulse oxygen saturation values through 1 minute to 24 hours and values of Apgar score at 1 and 5 minutes in newborns delivered at term in Cerro de Pasco (4340 m) and Lima (150 m). Pulse oxygen saturation was recorded in 39 newborns from Cerro de Pasco (4340 m) and 131 from Lima (150 m) at 1, 2, 3, 4, 5, 10, 15, 30 minutes and 1, 2, 8 and 24 hours after delivery. Apgar score was assessed at 1 and 5 minutes after birth. Neurological score was assessed at 24 h of birth by Dubowitz exam. Results Pulse oxygen saturation increased significantly from 1 to 15 min after birth at sea level and from 1 to 30 minutes at Cerro de Pasco. Thereafter, it increased slightly such that at 30 min at sea level and at 60 minutes in Cerro de Pasco it reached a plateau up to 24 hours after birth. At all times, pulse oxygen saturation was significantly higher at sea level than at high altitude (P < 0.01). At 1 minute of life, pulse oxygen saturation was 15% lower at high altitude than at sea level. Apgar score at 1 minute was significantly lower at high altitude (P < 0.05). Neurological score at 24 hours was also lower at high altitude than at sea level. Head circumference, and Apgar score at 5 minutes were similar at sea level and at high altitude (P:NS). Incidence of low birth-weight (<2500 g) at high altitude (5.4%) was similar to that observed at sea level (2.29%) (P:NS). Incidences of low pulse oxygen saturation (<30%), low Apgar score at first minute (<7) and low neurological score at 24 h (<19) were significantly higher at high altitude than at sea level (P < 0.0001; P < 0.0001; and P < 0.001, respectively). Conclusion From these analyses may be concluded that pulse oxygen saturation at 4340 m was significantly low despite the fact that births occurred at term. Apgar scores at first minute and neurological scores were also lower at high altitudes.